The causal impact of migration on US trade: Evidence from political refugees - Walter Steingress (Bank of Canada, 2017)
Immigrants can increase international trade by shifting preferences towards the goods of their country of origin and by reducing bilateral transaction costs. Using geographical variation across U.S. states for the period 2008 to 2013, I estimate the respective causal impact of immigrants on U.S. exports and imports. I address endogeneity and reverse causality by exploiting the exogenous allocation of political refugees within the U.S. refugee resettlement program that prevents immigrants from choosing the destination location. I find that a 10 percent increase in recent immigrants to a U.S. state raises imports from those immigrants' country of origin by 1.2 percent and exports by 0.8 percent.
Keywords: F14; F22; J61; 330; International topics; Regional economic developments